Numerical simulation and experimental verification of pitting corrosion propagation in sweet pipeline service - Zhenjin Zhu; Patrick J. Teevens; Huibin Xue; Y. Frank Cheng (Journal of Pipeline Science and Engineering, 2022)
This paper has numerically simulated and experimentally verified the pitting corrosion propagation inside a low-alloy carbon steel pipeline for sweet (CO2) petroleum service. In this study, a Finite-Element-Analysis-based mechanistic model was first developed to predict the transient dissolution rate of iron ion (Fe2+) from a pre-existing pit through solving the Nernst-Planck Equation. Specifically, the computational domain combines a hemispherical-shaped pit and a thin laminar boundary layer of an electrolyte solution. The mesh was generated using quadratic triangular elements in the Cartesian Coordinate System, and a moving mesh method was deployed to track the dynamic pitting propagation. The velocity distribution of the electrolyte solution was computed through solving the Navier-Stokes Equations. Distribution of electrochemical potentials was determined based on the Poisson Equation in consideration of electroneutrality whereas a Debye-Hückel approximation was applied to describe the variation of the potentials at the metal-solution interfaces by reason of the existence of the Electrical Double Layer. The distribution of the ionic concentrations of each participating chemical species was obtained through solving Fick’s Second Law. To verify the developed pitting propagation model, a laboratory testing system was established and a series of experimental tests were performed. The results demonstrate that the predicted pitting corrosion growth rates agree well with the experimental observations. The model described herein is able to predict pitting corrosion rates and induction times for the onset of pitting attack or passivation in a given sweet pipeline system set of operating conditions.